5‐(Trifluorovinyl)dibenzothiophenium Triflate: Introducing the 1, 1, 2‐Trifluoroethylene Tether in Drug‐Like Structures. Issue 18 (21st February 2023) - Feng, Zeyu; Marset, Xavier; Tostado, Jaime; Kircher, Johannes; She, Zhijie; Golz, Christopher; Mata, Ricardo A.; Simon, Martin; Alcarazo, Manuel
Abstract: This manuscript reports the synthesis and structure of an unprecedented sulfonium salt, 5‐(trifluorovinyl)dibenzothiophenium triflate, and its use as a versatile reagent for the introduction of the bioisosteric 1, 1, 2‐trifluoroethylene linker in drug‐like structures. The protocol developed consists of the reaction of this compound with alcohols and phenols to deliver a complete set of 1, 2, 2‐trifluoro‐2‐(alkoxy‐/aryloxy)ethyl sulfonium salts, which have been purified by column chromatography and fully characterized. Subsequent single electron reduction under mild photochemical conditions efficiently affords the corresponding fluoroalkyl radicals that are trapped either intra‐ or intermolecularly through their reaction with (hetero)arenes. Theoretical calculations are used to evaluate the conformational consequences derived from the presence of the CF2 −CHF tether. Abstract : A key reagent to introduce trifluoroethylene : A protocol for the connection of alcohols and (hetero)arenes via a trifluoroethylene linker has been developed. Key for the development of this procedure has been the synthesis of a sulfonium salt bearing a trifluorovinyl substituent. This reagent suffers the addition of alcohols to the activated double bond and subsequently generates alkyl fluoride radicals by mesolytic cleavage of the S−C bond after one electron reduction.